Investigation project: Representations about the professional role of recently graduated from the psychology career, state University of La Plata : Its relation with job insertion and performance - Salas, María Belén (2013)
In this paper we present a research that took place between 2010 and 2012 included in an investigation scholarship awarded by the State University of la Plata. It is about the problem with the transition between college and professional work. It is a part of the produced studies on the importance of social representations as factors that impact on the performance of specific activities. In this case it's about finding out the relations given among the representations about graduated professional role of the Psychology career and its job insertion and performance. The theoretical framework corresponds to Social Psychology and Guidance theories. Methodologically this is an exploratory and descriptive study, based on the 'triangulation' conception, of multiple type, that allows combining in the same investigation, different strategies, theoretical perspectives and sources; however qualitative techniques were prioritized to analyze data. Finally there are some considerations about the social representations concerning to the professional performance, mainly in the clinical field associated to education, and also to the problems of both situations over other fields
Keywords: Representations; Role; Psychologists; Work